Handbook of research on smart technology models for business and industry - Thomas, J. Joshua 1973-; Fiore, Ugo; Lechuga, Gilberto Perez; Kharchenko, Valeriy 1938- (IGI Global, 2020)
"This book discusses relevant abstract frameworks and the latest experimental research findings in theory, mathematical models, software applications, and prototypes in the area of smart technologies"--
Description based on title screen (IGI Global, viewed 07/25/2020)
Keywords: Artificial intelligence / Industrial applications; Automation; Big data; Business / Data processing